Comparative analysis of routing protocols for VoIP in a Wireless Mesh Backbone: a user perspective. (11th March 2009) - Queiroz, Saulo; Nascimento, Arlen; Mota, Edjair; Carvalho, Leandro S.G.; , Edson Nascimento
In this work we select AODV, OLSR and HWMP routing protocols and focus on how they can affect the Quality of user Experience (QoE) with respect to VoIP on a wireless backbone. We calculated QoE by using a reviewed version of the E-model. Since that parameter is strongly correlated with some stochastic network variables it presents stochastic behaviour too. So, we discuss important issues needed to estimate QoE based parameters in a trusty way. Results showed that the average QoE kept acceptable only under AODV routing as the number of VoIP traffic was increased in the network.